(untitled) (Biocenosis, 2023)
Modern society has led to a buy, use and throw-away culture, which has caused an almost uncontrollable plastic pollution crisis, to the extent of endangering the health and existence of living creatures. The situation is critical and controversial. On the one hand, there is the comfort generated by plastic in its various uses and forms, and on the other hand, the damage and prejudice to the health of living beings and the environment that its presence in practically the entire planet has begun to cause. A bibliographic search on the subject was carried out to know the status quo of planetary plastic pollution and find out the seriousness of the damage, which is mainly due to the transformation plastic goes through under the effects of climate by turning into microplastics until currently becoming nanoplastics. In conclusion, if general and specific actions are not taken such as non-use, reuse and recycling of plastics, the problem will continue to grow.